Analysis and investigations of inductive power transfer (IPT) systems in terms of efficiency and magnetic field distribution properties - R.M. Miśkiewicz; P. Anczewski; A.J. Moradewicz (Bulletin of the Polish Academy of Sciences: Technical Sciences, 2019)
The problems connected to developing inductive power transfer IPT systems in aspects of high efficiency and suppression of electromagnetic field (EMF) emission are discussed. It is shown how important it is to compensate for large leakage impedance of IPT coils (air transformer) to improve efficiency of high power transfer. Such compensation circuits operating with resonant frequencies at soft switching conditions additionally allow for reduction of switching losses in power semiconductor devices of converters. The consideration has been illustrated and verified by experimental results measured on two different test stands (50 kW with planar coils and with two 12 kW receiver coils) built in a laboratory of the Łukasiewicz Research Network – Electrotechnical Institute.